2021
DOI: 10.1029/2021jd034785
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Methane Emissions in California's San Joaquin Valley Inferred With Ground‐Based Remote Sensing Observations in the Summer and Winter

Abstract: Global concentrations of atmospheric CH 4 have substantially increased since 1750 due to the expansion of human agriculture, waste management, and fossil fuel usage (Dlugokencky et al., 2011). CH 4 is a 28 times stronger greenhouse gas than carbon dioxide (CO 2 ) on a century timescale and increased atmospheric CH 4 accounts for 25% of anthropogenic climate forcing to date (Etminan et al., 2016). CH 4 has also contributed to increases in tropospheric ozone, an air pollutant and short-lived greenhouse gas (Fior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 63 publications
(95 reference statements)
3
11
0
Order By: Relevance
“…Despite the general agreement between our results, previously published summertime observational studies, 11,41 and inverse model predictions for May-June conditions, 8 considerable disagreement remains regarding the temperature dependence of dairy emissions. While we observe a substantial increase in emissions with temperature (Figure S17), in line with Arndt et al (2018) 9 and the Maasakkers et al (2016) 37 parametrization, both observational studies 11 and recent inverse models 6,12 have suggested little to no variability between wintertime and summertime emissions in this region. Higher wind speeds during cooler months have been suggested to account for the lack of seasonality in emissions.…”
Section: Comparison With Previous Observational and Inverse Modeling ...supporting
confidence: 91%
See 4 more Smart Citations
“…Despite the general agreement between our results, previously published summertime observational studies, 11,41 and inverse model predictions for May-June conditions, 8 considerable disagreement remains regarding the temperature dependence of dairy emissions. While we observe a substantial increase in emissions with temperature (Figure S17), in line with Arndt et al (2018) 9 and the Maasakkers et al (2016) 37 parametrization, both observational studies 11 and recent inverse models 6,12 have suggested little to no variability between wintertime and summertime emissions in this region. Higher wind speeds during cooler months have been suggested to account for the lack of seasonality in emissions.…”
Section: Comparison With Previous Observational and Inverse Modeling ...supporting
confidence: 91%
“…While these inventories predict similar total emissions from dairy operations in California, 3 the spatial distributions of the published inventories vary considerably, especially in the southern SJV (Figure S18), with implications for their use as model priors in inversion-based analyses of methane emission sources. 8,12,43 Correlations between our measurements and the VISTA-CA dairy inventory (R = 0.51) are considerably stronger than those with the EPA 2016 livestock GHGI (R = 0.28) over the surveyed region (Figure 4). VISTA-CA uses detailed facilitylevel information (e.g., latitude−longitude) to spatially distribute dairy-related emissions in California, 3 and our measurements confirm that those efforts markedly improve the inventory's spatial representativeness relative to the EPA 2016 GHGI, which assigned emissions using general livestock probability maps based on the land type.…”
Section: Comparison Of Vista-ca and Epa-ghgi Inventoriesmentioning
confidence: 73%
See 3 more Smart Citations